Internalization of Slogans in Encouraging Change in Madrasah - Edi Sucipto; Sufyarma M; Sulastri Sulastri (International Journal of Educational Dynamics, 2022)
During the Indonesian struggle, there was the slogan "independence or death", then in the current era of government the slogans "work, work, work" and "Advanced Indonesia" appeared. In the Minangkabau indigenous people, the slogan "adat basandi sara`, sara` basandi kitabullah" also appeared. In the Madrasah there is the slogan independent Madrasah with achievements. If we look closely at it, we will encounter very many slogans somewhere in both communities and institutions, both formal and informal. Almost all create slogans for special purposes, all of which usually contain an invitation to do or not to do, think or not to think about, or even just as an uplifting for a community, institution, or even a nation for a common goal. This slogan is a stimulant that is designed systematically and in the context of Madrasah education to break attitudes that do not support change such as skeptic, lazy, uncreative, resigned, less innovative and others to be replaced with creative, innovative, diligent, implicit and other actions that support changes in various aspects of education in Madrasah. All the actions based on the slogan of change will eventually be able to pave the way to realize the expected goal in the slogan of education in Madrasah, namely "Madrasah Mandiri Berprestasi". There is no achievement, there is independence if the Madrasah component does not carry out actions that support that direction, one of which is never stagnant or silent, keep moving and make changes towards achievement and independence.